Tortoise tick Hyalomma aegyptium as long term carrier of Q fever agent Coxiella burnetii--evidence from experimental infection - Siroký, Pavel; Kubelová, Michaela; Modrý, David; Erhart, Jan; Literák, Ivan; Spitalská, Eva; Kocianová, Elena (Parasitology research, 2010)
The experimental study investigated the ability of tortoise tick Hyalomma aegyptium to play a role in forming and maintaining natural foci of Q fever. We tested the competence of H. aegyptium larvae to acquire Coxiella burnetii infection from mammals, serve as a C. burnetii vector between mammalian hosts, and be a long-term carrier of C. burnetii, including interstadial transmission. H. aegyptium larvae were allowed to feed on guinea pigs experimentally infected with C. burnetii. Engorged larvae molted to nymphs, some of which were preserved in 96% ethanol and later examined by polymerase chain reaction (PCR) using C. burnetii-specific primers (CBCOS, CBCOE). Prevalence of C. burnetii among these nymphs was 5.6% (n=235). Remaining nymphs then fed on other, C. burnetii-negative guinea pigs; and according to results of both, micro-agglutination reaction, and ELISA, they successfully transmitted C. burnetii to those new hosts. Detached engorged nymphs molted to adults, which were kept alive long term and then placed in 96% ethanol 383 days post-infection. Thereafter, they were examined by PCR in the same manner as were the nymphs. Prevalence of C. burnetii among adult H. aegyptium was 28.9% (n=90). According to our results, tortoise-specific ticks have indisputable potential in the epidemiology of Q fever natural foci.
Keywords: larva; Larva; zdroje nemoci; Disease Reservoirs; zvířata; Coxiella burnetii; Ixodidae; Guinea Pigs; morčata; Animals